2020
DOI: 10.1111/1471-0307.12723
|View full text |Cite
|
Sign up to set email alerts
|

Invitro digestion and absorption efficiency of homogenised milk lipids

Abstract: The effects of homogenisation, heat treatment and their order on in vitro gastric/pancreatic digestions, and in vitro absorption of milk lipids, expressed as free fatty acids, were investigated. Milk, cream or mixture of homogenised/heat‐treated cream and skim milk were subjected to gastric digestion at pH 2 or 6, followed by pancreatic digestion and cell absorption by CaCo‐2 cells. Heat treatment after or prior to homogenisation affected in vitro digestion efficiencies of milk lipids. The presence of milk pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…About 70% of the fatty acids in milk triacylglycerols are saturated, 25% are monounsaturated fatty acids (MUFA), and 5% are polyunsaturated fatty acids (PUFA) (Lopes et al, 2016;Abd El-Salam & El-Shibiny, 2020). Studies have shown nutritional components of milk fat, with an emphasis on conjugated linoleic acid (CLA), which consists of a group of fatty acids found predominantly in the milk (Agiral et al, 2020) and meat of ruminant animals, such as cows' (Ruiz et al, 2016), sheep (Nudda et al, 2014, Madruga et al, 2020, and goat (Apás et al, 2015). In milk, fatty acids can come from the diet, transported to the mammary gland or synthesized by the mammary epithelial cells (Vargas-Bello-Perez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 70% of the fatty acids in milk triacylglycerols are saturated, 25% are monounsaturated fatty acids (MUFA), and 5% are polyunsaturated fatty acids (PUFA) (Lopes et al, 2016;Abd El-Salam & El-Shibiny, 2020). Studies have shown nutritional components of milk fat, with an emphasis on conjugated linoleic acid (CLA), which consists of a group of fatty acids found predominantly in the milk (Agiral et al, 2020) and meat of ruminant animals, such as cows' (Ruiz et al, 2016), sheep (Nudda et al, 2014, Madruga et al, 2020, and goat (Apás et al, 2015). In milk, fatty acids can come from the diet, transported to the mammary gland or synthesized by the mammary epithelial cells (Vargas-Bello-Perez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Animal nutrition plays a fundamental role in the milk production system because in addition to being a determining tool for production, it influences the quality and is associated with a considerable share of the dairy herd (Lopes et al, 2011;Agiral et al, 2020). Some substances that modify milk's sensory characteristics are likely to result from intense changes in food compounds during digestion and intermediate metabolism from microbial and enzymatic processes (Addis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%